Photodeposition-Based Synthesis of TiO2@IrOx Core–Shell Catalyst for Proton Exchange Membrane Water Electrolysis with Low Iridium Loading - Hoffmeister, Darius; Finger, Selina; Fiedler, Lena; Ma, Tien Ching; Körner, Andreas; Zlatar, Matej; Fritsch, Birk; Bodnar, Kerstin Witte; Carl, Simon; Götz, Alexander; Zubiri, Benjamin Apeleo; Will, Johannes; et al. (Advanced Science, 2024)
The widespread application of green hydrogen production technologies requires cost reduction of crucial elements. To achieve this, a viable pathway to reduce the iridium loading in proton exchange membrane water electrolysis (PEMWE) is explored. Herein, a scalable synthesis method based on a photodeposition process for a TiO2@IrOx core–shell catalyst with a reduced iridium content as low as 40 wt.% is presented. Using this synthesis method, titania support particles homogeneously coated with a thin iridium oxide shell of only 2.1 ± 0.4 nm are obtained. The catalyst exhibits not only high ex situ activity, but also decent stability compared to commercially available catalysts. Furthermore, the unique core–shell structure provides a threefold increased electrical powder conductivity compared to structures without the shell. In addition, the low iridium content facilitates the fabrication of sufficiently thick catalyst layers at decreased iridium loadings mitigating the impact of crack formation in the catalyst layer during PEMWE operation. It is demonstrated that the novel TiO2@IrOx core–shell catalyst clearly outperforms the commercial reference in single-cell tests with an iridium loading below 0.3 mgIr cm−2 exhibiting a superior iridium-specific power density of 17.9 kW gIr−1 compared to 10.4 kW gIr−1 for the commercial reference.
CRIS-Team Scopus Importer:2024-06-21
Keywords: core–shell catalyst; iridium utilization; low loading; proton exchange membrane water electrolysis; thickness factor